Immediate Effects of Vocal Warm-Up on the Acoustic and Aerodynamic Parameters of Speech-Language Pathology Students - Merve Aydoğuş; Elçin Tadıhan Özkan (The Turkish Journal of Ear Nose and Throat)
Objective: Although vocal warm-up is vital for singers and other professional voice users, no consensus has been reached regarding its underlying physiological effects, especially for the non-singing community. Accommodating speech and language pathology (SLP) students, this research aimed to investigate the effects of vocal warm-up on the acoustic and aerodynamic parameters of voice. Material and Methods: A quasi-experimental, pre-test–post-test research design was used. A total of 28 SLP students performed a 20-minute session of vocal warm-up based on breathing, stretching, phonation, and resonance exercises. Data analysis consisted of instrumental analysis in which the Multidimensional Voice Programme (MDVP) and Phonatory Aerodynamic System (PAS) were used to measure acoustic and aerodynamic parameters before and after vocal warm-up. Results: A significant decrease in jitter and shimmer values was detected after the vocal warm-up period. Additionally, significantly higher values were found in the subglottal pressure estimate. Conclusion: Following vocal warm-up, acoustic and aerodynamic parameters improved to normal values. The findings indicate that vocal warmups improve the objective voice quality.